Risk Factors Analysis of Maternal Emergencies and Optimization of Maternal and Child Health Handbook (MCH Handbook) Utilization : Sarimahi Village, Ciparay Subdistrict, Bandung Regency, Indonesia, 2025 - Dewi Puspita; Indah Rahayu (International Journal Of Health Science, 2025)
Maternal emergencies remain a significant public health concern and are one of the main contributors to the persistently high maternal mortality rate in Indonesia. Early detection of pregnancy-related complications is essential to reducing these risks, and one effective approach is by strengthening maternal health literacy. The Maternal and Child Health (MCH) Handbook plays a vital role in this process as it functions both as an educational medium and as a comprehensive health record for mothers, covering the continuum of care from pregnancy, delivery, to the postpartum period. This study was conducted with the objective of analyzing factors associated with maternal emergencies, particularly focusing on the level of understanding and utilization of the MCH Handbook among postpartum mothers. A case-control study design was applied, involving a total of 80 respondents, with 40 assigned to the case group and 40 to the control group. The participants were randomly selected from Sarimahi Village. Data collection was carried out using structured questionnaires, and statistical analysis was performed employing the Chi-Square test. The findings of the study revealed a significant association between the level of understanding of the MCH Handbook and the occurrence of maternal emergencies (p = 0.001). Similarly, a significant relationship was observed between the level of utilization of the MCH Handbook and maternal emergencies (p = 0.002). Additional factors identified as contributing to maternal emergencies included maternal age, education level, parity, pregnancy interval, and a history of complications in previous pregnancies. The study concludes that a higher level of understanding and active utilization of the MCH Handbook play an essential role in preventing maternal emergencies. Therefore, efforts to improve maternal health literacy through the optimized and consistent use of the MCH Handbook should be actively promoted and strengthened within community health programs.